A CRITIQUE OF THE AVAILABLE DEBT RELIEF MEASURES AFFORDED TO NINA DEBTORS IN THE WAKE OF TRANSFORMATIVE CONSTITUTIONALISM AND INTERNATIONAL TRENDS (The Pretoria Student Law Review, 2021)
Insolvency law is well-established throughout the world and while there are measures in place for dealing with debtors who find themselves in varied circumstances, the issue of relief measures afforded to no- income, no-asset (NINA) debtors has posed quite an issue for many countries, South Africa particularly. When approaching bona fide NINA debtors, the concepts of equality and justice come into play with consideration to the socio-economic circumstances of many in South Africa, our woeful past, and the current ideals of transformative constitutionalism. This paper delves further into this issue and conclusively recommends that legislation be developed in line with other countries such as New Zealand and Kenya.
Keywords: NINA debtors; debt relief; transformative constitutionalism; equality